STRATEGI PENINGKATAN SUMBER DAYA MANUSIA KREATIF DAN INOVATIF PADA UKM BATIK SEMARANGAN (Studi Di Kampung Batik Semarang) - C Tri Widiastuti; Rahmatya Widyaswati; Rita Meiriyanti (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2019)
Indonesia has changed the era of the industrial revolution 4.0, a revolution marked by a technological revolution that brought many changes and risks, one of which involved purchases. In this era, human resources are the key to the success of a business, therefore a strategy is needed to improve the quality of human resources. This research will analyze the human resources in Semarang batik village. The purpose of the analysis of strategies to improve human resources into superior human resources, competence and adequate quality. This study used descriptive qualitative method. Research site in Semarang Batik Village. Research informants about batik businesses, employees and policy makers in the Rejomulyo sub-district of Semarang. The method of data collection is done by using interview techniques on informants, literature studies and observations. Data analysis techniques with reduction, data presentation and drawing conclusions Test the validity of the data using source triangulation. The results of the analysis of this study revealed that research on batik requires several strategies to improve the quality of human resources, these strategies provide motivation, increase competencies, certification of skills, best practices and exhibitions.